Synthesis and Identification of Some New bis Oxazepinedione and bis Benzoxazepinedione Compounds via Cyclization Reaction for Some bis Schiff Bases - Beebany, Shakhawan; Jasim, Saad Salem; Arslan, Sevgi Samih Hidayet (Sulaimani Journal for Pure and Applied Sciences, 2023)
This study was involved synthesis of new bis oxazepinedione and bis benzoxazepinedione compounds, derived from Schiff bases a(1-5). These Schiff bases were prepared from hydrazine and diethyl succinate using ethanol as solvent. The prepared Schiff bases have been undergone to reaction with maleic anhydride and phthalic anhydride to form bis oxazepinedione b(1-5) and bis benzoxazepinedione b(6-10) derivatives. The newly synthesized compounds were characterized using spectroscopic techniques such as Carbon, Hydrogen and Nitrogen (CHN) Elemental Analysis, Fourier transform infrared (FT-IR) spectroscopy and proton nuclear magnetic resonance ( 1H-NMR). The molecular orbital package (MOPAC) method has been used to calculate heat of formation (HF) and steric Energy (SE) for all of the synthesized chemicals. The (SE) calculations were performed using the molecular modelling (MM2) method. The MOPAC and MM2 methods are available in CS- Chemoffice-version 6.0 contains. The results indicated that compounds (a3, a4, b5 and b9) were shown high stability and less steric effect. This may relate to the presence of donating groups in the structure [OCH3 and N(CH3)2 ].
Keywords: Oxazepinedione; Schiffbase; Succinohydrazide; Schiff cyclization